2005
DOI: 10.1007/s11268-005-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Geochemical Background and Anthropogenic Load by Bioaccumulation of Microelements in Fish

Abstract: Comparative characteristic of several microelements (Ni, Cu, Sr, Al, Zn, Co, Mn, Pb, Cd, Hg, As) found in fish (case study of breams in the Volga basin reservoirs) is presented. Regularities of accumulation of these elements in fish depending on their concentration in the water are analyzed. Main disturbances in fish caused by the accumulation of microelements in their organs and tissues are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The literature data and the results of our study show that the metal concentrations in fish tissues vary widely depending on the sampling area. It is known that heavy metal contents in aquatic organisms are influenced not only by the anthropogenic load on the water body, the concentration of elements, and the duration of exposure, but also by the hydrochemical factors of the aquatic environment, because the solubility of a number of trace elements located in hard-to-reach compounds in silts depends on the oxygen level, pH, and other environmental parameters [ 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature data and the results of our study show that the metal concentrations in fish tissues vary widely depending on the sampling area. It is known that heavy metal contents in aquatic organisms are influenced not only by the anthropogenic load on the water body, the concentration of elements, and the duration of exposure, but also by the hydrochemical factors of the aquatic environment, because the solubility of a number of trace elements located in hard-to-reach compounds in silts depends on the oxygen level, pH, and other environmental parameters [ 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of advanced clean coal combustion technologies for coal-fired power plants results not only in atmospheric chemical pollution but also in the pollution of water ecosystems. Chemical pollutions change the quality of lake waters, accumulate in hydrobionts, and interfere with the biodiversity and structure of the lakes populations (Sunda, Guillard 1976, Nikanorov, Zhulidov 1991, Heaven et al 2000, Cardwell et al 2002, Tulonen et al 2006, Moiseenko et al 2005, Pastukhov 2012, Moiseenko, Gashkina 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The research (Chale 2002) has shown that concentrations of trace metals of water were lower than that in fish tissues, which is consistent with our research. The self-cleaning ability from water ecosystems where aquatic organisms a purify waters polluted plays a role here (Moiseenko et al 2005, Alimov et al 2013. As compared to the aquatic environment, the contents of chemical elements in bottom sediments are an order of magnitude higher (Table 4).…”
Section: Conditions Of the Aquatic Environment And Bottom Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…LF Shepeleva, ZA Samoilenko and GS Taran are the most known scientists studying the floodplain vegetation [44][45][46][47][48][49][50]. Animals and birds were studied by AM Adam, SS Moskvitin and AA Maksimov [51][52][53][54][55][56][57][58]. Many scientists (NF Vyltsan, GD Dymina, AV Ogorodnikova, AI Boynov, VN Tyurin and PS Kuzin) studied the floodplain resources and hydrological peculiarities and problems [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Previous Researchmentioning
confidence: 99%